2005
DOI: 10.1007/s00244-004-0054-8
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide and Pathogen Contamination of Vegetables in Ghana’s Urban Markets

Abstract: The objective of the study was to determine and compare the current level of exposure of the Ghanaian urban population to hazardous pesticide and fecal coliform contamination through the consumption of fresh vegetables produced in intensive urban and periurban smallholder agriculture with informal wastewater irrigation. A total of 180 vegetable samples (lettuce, cabbage, and spring onion) were randomly collected under normal purchase conditions from 9 major markets and 12 specialized selling points in 3 major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
167
3
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(192 citation statements)
references
References 4 publications
16
167
3
6
Order By: Relevance
“…Institute (IWMI) office in Accra with several national and international partners has undertaken a number of studies under its projects CPWF38 and 51, to ascertain and reduce the potential health hazards associated with the practice (Keraita et al 2007;Keraita & Drechsel 2004;Amoah et al 2006Amoah et al , 2007aObuobie et al 2006). This work is an extension of the IWMI studies and aims at quantifying the doi: 10.2166/wh.2008.118 health risks associated with the practice using the Quantitative Microbial Risk Assessment (QMRA) approach.…”
Section: Over the Years The International Water Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Institute (IWMI) office in Accra with several national and international partners has undertaken a number of studies under its projects CPWF38 and 51, to ascertain and reduce the potential health hazards associated with the practice (Keraita et al 2007;Keraita & Drechsel 2004;Amoah et al 2006Amoah et al , 2007aObuobie et al 2006). This work is an extension of the IWMI studies and aims at quantifying the doi: 10.2166/wh.2008.118 health risks associated with the practice using the Quantitative Microbial Risk Assessment (QMRA) approach.…”
Section: Over the Years The International Water Managementmentioning
confidence: 99%
“…Microbial investigations undertaken so far on wastewater reuse in Accra have focused on the quantification of helminths eggs and faecal coliforms (FC) (Keraita & Drechsel 2004;Obuobie et al 2006;Amoah et al 2006Amoah et al , 2007a. For purposes of our assessment, we chose rotavirus and Ascaris lumbricoides as the model organisms.…”
Section: Choice Of Pathogens and Justificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Causes of breast cancer, reduced sperm count, male sterility and death are well documented as a result of pesticide ingestion (Carvalho, 2006). Studies in Ghana indicated the presence of pesticide residues in vegetables, fruits and fish, at locations known for pesticide usage (Ntow, 2005;Amoah et al, 2006;Mensah et al, 2004;Aboagye, 2002). Growth in agrobased industries, increase in agriculture activities, improper storage and lack of sound disposal facilities have caused contamination of soil and water bodies resulting in a rapid increase in the number of pesticides into the Aquatic ecosystem (FAO/WHO, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Fresh produce grown in such ways are often contaminated [4] with e.g. helminthes eggs (Amoah et al, 2006;Keraita et al, 2008a), as well as soil, as a consequence of repeated application of polluted water (Keraita et al, 2007a). Several constraints hamper strategies to reduce microbial risk.…”
Section: Farm Animals and Produce Safety Issuesmentioning
confidence: 99%